ANALYSIS OF PUMP PRESSURE REDUCTION IN THE MAIN COOLING SYSTEM ENGINE ON THE MT. FORTUNE PACIFIC XLIX - Saputra, Dimas; Irawan, Bambang (Meteor STIP Marunda, 2025)
Maintenance of seawater pumps on ships is vital, especially for the Sea Water Service Main Engine unit, which is the heart of seawater circulation on ships. The MT. Fortune Pacific XLIX experienced problems with the main engine seawater cooling pump, while sailing from the port of Sabang to the port of Tanjung Uban. This paper aims to identify the factors causing the pressure drop in the centrifugal pump of the main engine seawater cooling system on the MT. Fortune Pacific XLIX, determine the impact, and provide the best solution to prevent another pressure drop in the centrifugal pump of the main engine seawater cooling system. This paper uses qualitative and quantitative methods using descriptive data analysis techniques and USG methods. Based on the results of the data in this paper, it was found that the lack of maintenance procedures for the centrifugal pump of the main engine seawater cooling system was due to the crew's lack of discipline in monitoring the maintenance schedule in accordance with the Plan Maintenance System (PMS) set by the company. The cause of damage to the impeller of the centrifugal pump of the main engine seawater cooling system was due to clogging of dirt or debris in the impeller chamber that entered through the sea chest, resulting in friction and causing the pump impeller to wear out or become damaged.